The responsiveness of an Australian science teacher professional development program to the needs of local and developing country science educators. - Thair, Micheal J. (Curtin University, 1999)
Many developing countries do not have in place high quality science education postgraduate programs; consequently, teachers from these countries are enrolling in programs in developed countries such as Australia, the United Kingdom and the United States. A number of authors have raised concerns that these programs are not responsive to the professional development needs of developing country teachers, suggesting that participants remain unaffected by their overseas experiences. There are similar concerns about teachers from developed countries also being unable to implement new ideas for teaching in their classrooms. This may be due to a number of reasons including feelings of powerlessness in overly prescriptive programs, high demands on teachers' time, a lack of resources, and a general lack of encouragement. These issues raise a number of questions about the nature of teacher professional development and in particular about appropriate ways to implement these programs.In response to these concerns, this thesis examines the responsiveness of a science education postgraduate program conducted in Australia to the needs of local and developing country participants and the influences of differences between Australian and developing country science teachers in terms of their professional, personal and social development. The assumption being that programs in developed countries are largely orientated towards the needs of home-country students. The conceptual framework for the thesis is a recent approach to science teacher professional development that provides a holistic perspective on science teacher professional development, focusing not only on individual teachers but also on the educational environment in which they operate. This perspective acknowledges the complexities of school environments and considers teachers' beliefs and feelings.The research focuses on participants from Australian and Indonesian who have completed a science education postgraduate program in Western Australia at the Science and Mathematics Education Centre (SMEC) located at Curtin University of Technology in Western Australia. These two groups were chosen because between 1988 and 1995 they were the predominant nationalities participating in SMEC programs. The research methodology and use of quantitative and qualitative research instruments was in keeping with the holistic conceptual framework adopted for the study and follows recent trends in teacher professional development research which have seen a broadening of research methodologies. The instruments used included a postal questionnaire, classroom observation schedule and structured interviews.The research findings indicated that the Indonesians have different needs to their Australian counterparts in terms of their professional, personal and social development. These differences included the Indonesians' strong beliefs in and use of didactic and formal teaching methodologies, limitations in Indonesian classrooms on the introduction of new teaching activities, a more centralised and formal education system in Indonesia in contrast to the increasing autonomy seen in Australia, and a more flexible teacher professional development approach in Australia focussing on personal development, as opposed to the curriculum and assessment focus seen in Indonesia. In addition, there are vast differences between the Indonesian and Australian education systems and these differences were seen to reinforce many of the different beliefs and practices between the Indonesian and Australian participants.The study suggests that the Australian participants are able to implement teaching approaches and theoretical frameworks included in their postgraduate studies at SMEC; however, the conclusions highlight the limitations of expecting that this can occur for developing country participants. In examining approaches in overcoming these limitations, it was concluded that a range of minor interventions or modifications to program design and content would be insufficient and a number of key indicators were identified that point to the responsiveness of programs for developing country participants. These indicators included the need for host institutions to be fully conversant with the classrooms and social contexts of developing country participants, constructivist pedagogical approaches to program design, planning and implementation, and the necessary flexibility to maintain academic rigour in postgraduate science education programs while incorporating unfamiliar education notions and frameworks from developing countries.